Análise imunohistoquímica do efeito do Resveratrol em ratos submetidos à periodontite induzida - Bertoli, Manuela Gomes (2018)
Periodontitis is an inflammatory and infectious disease that affects the tissues supporting the teeth destroying the tissues of periodontal support, including alveolar bone. In search of new means of treatment to avoid the loss of bone tissue, natural drugs with antiinflammatory capacity that have a good immune response have been increasingly studied. Resveratrol (RESV) is a polyphenol that has antioxidant and anti-inflammatory properties and is capable of promoting immunomodulatory effects on the host's response. Therefore, the objective of this study was to evaluate the effect of RESV in rats submitted to induced periodontitis. Ligatures were inserted into the mesial of the right and left upper second molars of Wistar rats (± 400 g) for a period of 15 days. Then the animals were randomly allocated into two groups with two experimental times of 14 and 30 days. Group Test (T), contains RESV + β-ciclodextrina (β-cd), as β-cd is the placeb solution responsable for the RESV encapsulation, and group Control (C), only β-Cd. The medication was administrated daily orally by gavage, with a daily dose of 10mg / mL / kg of the Group T medication or the solution of Group C, according to the groups during the 14 and 30 day evaluation period. We obtained as a result the positive effect of resveratrol mainly in the time of 30 days of medication, forming osteoprogenitor cells, proving its efficiency in the induction of bone formation, concluding then that the use of this medication may be a possibility of treatment for periodontitis.